1990
DOI: 10.1055/s-2008-1040481
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Regulation of Hepatic Glutathione

Abstract: Glutathione plays a key role in the liver in detoxification reactions and in regulating the thiol-disulfide status of the cell. Glutathione synthesis is regulated mainly by the availability of precursor cysteine and the concentration of glutathione itself which feeds back to regulate its own synthesis. Degradation of hepatic glutathione is principally regulated by the efflux of reduced and oxidized glutathione into both sinusoidal plasma and bile. In addition, glutathione may be consumed in conjugation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
9

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(75 citation statements)
references
References 27 publications
0
66
0
9
Order By: Relevance
“…Earlier studies from our laboratory reported a 50% decrease in cochlear GSH (expressed as nmoledmg tissue) following cisplatin ototoxicity Rybak et al 1995). Although GSH (expressed as nmoledmg protein) depletion was 20% following cisplatin administration, such depletion can impair the cell's defense against the toxic actions of reactive oxygen species and may lead to cell injury (Deleve & Kaplowitz 1990). The protection against cisplatin ototoxicity with MTBA treatment was comparable to that seen with sodium thiosulfate in guinea pigs (Otto rt al.…”
Section: Discussionmentioning
confidence: 94%
“…Earlier studies from our laboratory reported a 50% decrease in cochlear GSH (expressed as nmoledmg tissue) following cisplatin ototoxicity Rybak et al 1995). Although GSH (expressed as nmoledmg protein) depletion was 20% following cisplatin administration, such depletion can impair the cell's defense against the toxic actions of reactive oxygen species and may lead to cell injury (Deleve & Kaplowitz 1990). The protection against cisplatin ototoxicity with MTBA treatment was comparable to that seen with sodium thiosulfate in guinea pigs (Otto rt al.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, as schematically drawn in Figure 2, overexpression of Bcl-2 and point Figure 1. Proposed scheme of genotoxic events in the multistage process of biliary carcinogenesis metabolic line of defense in eliminating hydrophobic and carcinogenic compounds [31,32]. Bioactivation of lipophilic compounds by cytochrome P-450S can result in the generation of reactive oxygen compounds.…”
Section: Stage Iii: Dysregulation Of Dna-repair and Apoptosis Leadingmentioning
confidence: 99%
“…In human cholangiocarcinoma downregulation of UGT1A4 and UGT1A10 has been demonstrated to be an early marker of biliary carcinogenesis [31]. GSH, which is secreted by hepatocytes into bile, maintains molecules in the reduced state, and similar to UGT, also participates in the detoxification of different carcinogenic molecules [32]. The inability to remove damaging cellular carcinogens predisposes cells to genetic alterations which can be followed by point-mutations of mutations of p53 and K-ras may inhibit apoptosis of DNA damaged cholangiocytes, permitting survival of the mutated cell line with progress to CC [39].…”
Section: Stage Iii: Dysregulation Of Dna-repair and Apoptosis Leadingmentioning
confidence: 99%
“…30) GSH is an endogenously synthesized tripeptide thiol that plays an essential role in maintaining redox status, extinction of free radicals, conjugation/detoxification reactions, apoptosis, and cell signaling. 31,32) Increased ROS and decreased GSH levels contribute to loss of MMP, which is directly associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%